1987
DOI: 10.1111/j.1440-1827.1987.tb02265.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperlipidemia on Glomerular Sclerosis in Unilateral Nephrectomized Rats

Abstract: The development of focal segmental glomerular sclerosis (FSGS) and its relation to hypertriglycemia were studied in unilateral nephrectomized rats. Group A (n=6), fed standard rat chow supplemented with 20% beef tallow and 0.6% cholic acid for 25 weeks, showed evidence of hypertriglycemia (109.4 ±4.3 mg/dl). Group B (n=7) was given the same rat chow as group A, but they did not have high serum levels of TG (66.4 ±2.3 mg/dl). Group C (n = 6) were the controls and their serum TG levels were 53.0 ±3.8 mg/dl. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In rats fed on different oils, or butter, decline in glomerular fi ltration rate (GFR) was found to be greatest in those receiving butter, perhaps because of a higher percentage of saturated fat. It has been convincingly demonstrated that rats with chronic hyperlipidemia and hypercholesterolemia develop glomerulosclerosis in kidneys (51,55,53). Hyperlipidemia was also supposed to be associated with chronic tubulointerstitial damage (15,56).…”
Section: Discussionmentioning
confidence: 99%
“…In rats fed on different oils, or butter, decline in glomerular fi ltration rate (GFR) was found to be greatest in those receiving butter, perhaps because of a higher percentage of saturated fat. It has been convincingly demonstrated that rats with chronic hyperlipidemia and hypercholesterolemia develop glomerulosclerosis in kidneys (51,55,53). Hyperlipidemia was also supposed to be associated with chronic tubulointerstitial damage (15,56).…”
Section: Discussionmentioning
confidence: 99%
“…It has been convincingly demonstrated that rats with chronic hyperlipidemia and hypercholesterolemia develop glomerulosclerosis in kidneys without immune complex disease (14,34,45,53). The present study confirms these data.…”
Section: Discussionmentioning
confidence: 99%